Ozone treatment regulated the anti-exercise fatigue effect of fresh-cut pitaya polyphenol extracts - Li, Chen; Wu, Zhaoxia; Yang, Xiaofei (Frontiers in Nutrition, 2024)
The anti-exercise fatigue effect of plant polyphenols is closely related to the content, composition, and extractability of phenolic substances. According to our previous findings, ozone treatment significantly affected the biological effects of fresh-cut pitaya polyphenols. Therefore, this study used C57BL/6J mice to explore the regulatory mechanism of ozone treatment on the anti-exercise fatigue effect of fresh-cut pitaya polyphenol extract. The result showed that fresh-cut pitaya polyphenols treated with ozone (OP) have a better effect. Compared with the untreated group, the exhaustion time of the OP group was 11.86% longer, the total antioxidant capacity was 54.17% higher, the MDA content was 32.8% lower, and the liver glycogen content was 85.71% higher. The OP group also better regulated substrate metabolism, protecting muscle and visceral weight. The results of RT-PCR were consistent with the results of network pharmacology, and the expression of PI3K and AKT was activated, while SRC and STAT3 were down-regulated. Furthermore, pitaya polyphenols have been demonstrated to exert anti-fatigue effects by increasing the diversity of gut microbiota species. In summary, ozone treatment is a feasible way to improve the nutrition of polyphenols.